1989
DOI: 10.3109/00016348909013286
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Diagnosis and Early in Utero Treatment of Obstructive Uropathy

Abstract: The earliest diagnosis and treatment of obstructed fetal bladder is reported. Placement of vesico-amniotic shunt at 14.5 weeks of gestation enabled preservation of bilateral renal function and maintenance of normal amniotic fluid volume with normal pulmonary development. The shunt functioned adequately for more than 12 weeks. At birth, a mild 'prune' belly was the only deformity noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
1
8
0
3
Order By: Relevance
“…This is supported by previous studies involving 31 cases of fetal megacystis ( Table 1) which showed that in five of seven cases treated by bladder drainage between 10 and 14 weeks, the postnatal renal function was normal in four and reduced to 50% in one 2,6,7,8 . In a …”
Section: Discussionsupporting
confidence: 77%
“…This is supported by previous studies involving 31 cases of fetal megacystis ( Table 1) which showed that in five of seven cases treated by bladder drainage between 10 and 14 weeks, the postnatal renal function was normal in four and reduced to 50% in one 2,6,7,8 . In a …”
Section: Discussionsupporting
confidence: 77%
“…However, there are a few published case reports of children with LUTO that were subjected to early vesico-amniotic shunting and survived until birth with normal renal function what raises the question of the benefit of an earlier treatment [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Au moment du diagnostic, la moyenne d'âge maternel était de 31 ans (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) La moyenne du diamètre longitudinal de la vessie au moment du diagnostic était de 20 mm .…”
Section: Résultatsunclassified